Religion, 'nature' and environmental ethics in ancient India: archaeologies of human:non-human suffering and well-being in early Buddhist and Hindu contexts. Issue 4 (7th August 2016) - Shaw, Julia
ABSTRACT: This paper assesses archaeology's contribution to debates regarding the ecological focus of early Buddhism and Hinduism and its relevance to global environmentalism. Evidence for long-term human:non-human entanglement, and the socio-economically constructed element of 'nature' on which Indic culture supposedly rests, challenges post-colonial tropes of India's utopian, 'eco-friendly' past, whilst also highlighting the potency of individual human:non-human epistemologies for building historically grounded models of Indian environmentalism. For early Buddhism, I mediate between two polarized views: one promoting the idea of 'eco-dharma' as a reflection of Buddhism's alignment with non-violence ( ahiṃsā ), and the alleviation of suffering ( dukkha ); a second arguing that early Buddhist traditions have been misappropriated by western environmentalism. I argue that the latter view subscribes to canonical models of passive monks removed from worldly concerns, despite archaeological evidence for socially-engaged monastic landlordism from the late centuriesbc . Others cite this evidence only to negate Buddhism's eco-credentials, thereby overlooking the human:non-human entanglement theme within modern environmental discourse, while the predominant focus on non-human suffering overlooks convergences between modern and ancient ecological ethics and environmental health. Case studies include examples of Buddhist land and water management in central India, set within discussions of human v. non-human-centric frameworks of well-being and suffering, purity and pollution, and broader Indic medico-ecological epistemologies, as possible models for collective responses to environmental stress.